Public awareness and understanding of stem cell treatments available in Saudi Arabia and their trust in hospitals and research centers involved in stem cell research—a cross sectional study - Aboalola, Doaa; Ramadan, Majed; Baadhaim, Moayad; Alsiary, Rawiah; Badraiq, Heba; Alghamdi, Tariq; Zakri, Samer; Aboulola, Neda; Falatah, Tark; Malibari, Dalal (Frontiers in Public Health, 2024)
Although stem cell research and therapeutic applications hold great promise for medical advancements, and have rapidly progressed globally, there remains a lack of genuine public awareness of the status of this subject in Saudi Arabia. Successful integration of stem cell therapy into healthcare relies on public awareness, understanding, and trust.Therefore, we aimed in this cross-sectional study to assess the public's knowledge, awareness, trust, support, participation, and confidence in stem cell treatments and centers involved in it. Materials and methods: A voluntary questionnaire of 20 questions was distributed randomly via social media outlets. Results: 3,584 individuals participated in the survey, with approximately half of them falling within the age range of 35-50 years (46.71%). Majority of the participants, 90.71%, would like to know more about stem cell therapy and more than half of the participants (56.94%) were unfamiliar with the idea, and a comparable proportion (50.41%) expressed concerns about the safety of stem cell therapy. A lower level of awareness, indicated by a score of 5, was evenly distributed across all age groups and genders. However, regardless of gender, older participantsespecially those 50 years of age or older-tended to report higher levels of confidence, trust, and support than participants in other age groups. Moreover, trust, support, participation, and confidence score for those attained high school or less was statistically significantly lower than those attained master's or PhD degree. Of the participants, 33.57% had either received stem cell therapy themselves or known someone who had; about 24.07% of them reported that it was a cosmetic type of treatment. Conclusions:The study emphasizes the persistent need for awareness and educational initiatives to minimize the lack of public awareness and understanding of approved stem cell treatments in Saudi Arabia. It advocates for increased education, transparency, and communication to bridge knowledge gaps and enhance public trust to ensure the understanding of successful treatment.Although stem cell research and therapeutic applications hold great promise for medical advancements, and have rapidly progressed globally, there remains a lack of genuine